G12 From premanifest to manifest Huntington's disease: a 2-year follow-up study with magnetic resonance spectroscopy at 7 Tesla. (29th August 2012) - van den Bogaard, SJA; Dumas, EM; Teeuwisse, W; Kan, HE; Webb, A; van Buchem, MA; Roos, RAC; van der Grond, J
Abstract : Background: Previous cross-sectional magnetic resonance spectroscopy (MRS) studies in Huntington's disease (HD) have demonstrated differences in metabolite concentrations compared to controls in several regions of interest, especially the putamen and caudate nucleus. It has been suggested that metabolite changes could be used as biomarker in future therapeutic trials. The aim of the present study was to assess metabolite changes in both premanifest and early HD over a 2 year follow-up period using MRS at 7 Tesla. Methods: In 13 HD gene carriers (10 premanifest and 3 manifest HD) proton MRS was performed at baseline and after 24 months. At follow-up, four of the premanifest HD gene carriers had progressed into manifest HD, as assessed by clinical measures. 7T MR proton spectroscopy was performed in three regions of interest; the caudate nucleus, putamen and prefrontal cortex. Six metabolites were quantified for each region at each time point. Statistical analysis was performed using paired t-tests. Results: In the caudate nucleus a decrease in creatine (p=0.032) and myo-inositol (p=0.006) concentrations was observed. A significant decrease in the putamen was seen in the total N-acetylaspartate (tNAA) (p=0.022) and choline concentrations (p=0.007). Premanifest HD converters showed higher rates of tNAA decrease in the putamen (p<0.003) than non-converting premanifest HD. Conclusion: Over a period of 2 years we have demonstrated metabolite changes in the caudate nucleus and putamen of HD gene carriers around disease onset. This demonstrates the potential of MRS for providing a biomarker of disease progression and for evaluating future therapeutic interventions.